Bike boys, drag queens & superstars : avant-garde, mass culture, and gay identities in the 1960s underground cinema - Suárez, Juan Antonio (Bloomington : Indiana University Press, 1996)
At the confluence of experimental art and the gay subculture of early 1960s New York, Juan Suárez discovers a postmodern, gay-influenced aesthetic that "recycles" popular culture. Filmmakers Kenneth Anger, Jack Smith, and Andy Warhol epitomize this sensibility, combining the influences of European avant-garde movements, comic books, rock 'n' roll, camp, film cults, drag performances, fashion, and urban street cultures.
Avant-garde and mass culture: mapping the dialectic -- The American underground as a cultural formation: practices, institutions, and ideologies -- The 1960s underground as political postmodernism: from the new sensibility to gay cultural activism -- Pop, queer, or fascist? The ambiguity of mass culture in Kenneth Anger's Scorpio Rising -- Drag, rubble, and "Secret Flix": Jack Smith's avant-garde against the lucky landlord empire -- The artist as advertiser: stardom, style, and commodification in Andy Warhol's underground films.
Includes bibliographical references (pages 331-343) and index.
Filmography: pages 317-320.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Anger, Kenneth -- Criticism and interpretation; Smith, Jack, -- 1932-1989 -- Criticism and interpretation; Warhol, Andy, -- 1928-1987 -- Criticism and interpretation; Anger, Kenneth; Smith, Jack, -- 1932-1989; Warhol, Andy, -- 1928-1987; Anger, Kenneth -- Criticism and interpretation; Smith, Jack, -- 1932-1989 -- Criticism and interpretation; Warhol, Andy, -- 1928-1987 -- Criticism and interpretation; Experimental films -- United States -- History and criticism; Homosexuality in motion pictures; Drag queens in motion pictures; Popular culture -- United States; Popular culture; Homosexuality in motion pictures; Popular Culture; United States; Homosexualité au cinéma.; Culture populaire -- États-Unis.; Culture populaire; popular culture; PERFORMING ARTS -- Film & Video -- Reference; Experimental films; Homosexuality in motion pictures; Popular culture; United States; Untergrundfilm; Homosexualität; Massenkultur; USA; Homoseksualiteit; Experimentele filmkunst; Experimental films -- United States -- History and criticism; Homosexuality in motion pictures; Popular culture -- United States; Experimentfilm -- Förenta staterna; Homosexualitet i filmen; Geschichte 1960-1970.; Criticism, interpretation, etc; Film criticism; Critiques cinématographiques.